2019
DOI: 10.1002/clc.23235
|View full text |Cite
|
Sign up to set email alerts
|

Initial rivaroxaban dosing in patients with atrial fibrillation

Abstract: Background Rivaroxaban is a non‐vitamin K oral anticoagulant and has been approved for prevention of stroke and systemic embolism in patients with non‐valvular atrial fibrillation (AF). Current labeling recommends 20 mg once a day (q.d.) as a standard dose and a reduced dose of 15 mg q.d. in patients with renal impairment. Hypothesis The aim of this study was to analyze the adherence to current labeling concerning initial rivaroxaban dosing and to determine whether potential lack of such adherence is medically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…In the Berlin Atrial Fibrillation Registry, under-dosing of apixaban and rivaroxaban at stroke onset was associated with old age, which is in line with prospective AF registries like ORBIT AF II, including only a subset of patients with prior (but not acute) ischemic stroke [ 14 17 ]. Compared to on-label dosing, under-dosing of apixaban or rivaroxaban was not significantly associated with stroke severity on hospital admission or at hospital discharge.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In the Berlin Atrial Fibrillation Registry, under-dosing of apixaban and rivaroxaban at stroke onset was associated with old age, which is in line with prospective AF registries like ORBIT AF II, including only a subset of patients with prior (but not acute) ischemic stroke [ 14 17 ]. Compared to on-label dosing, under-dosing of apixaban or rivaroxaban was not significantly associated with stroke severity on hospital admission or at hospital discharge.…”
Section: Discussionsupporting
confidence: 58%
“…Treating physicians are advised to prescribe the guideline-recommended in-label NOAC dosage in each patient, taking patients' age (for dabigatran, apixaban, and edoxaban), renal function (dabigatran, apixaban, rivaroxaban, and edoxaban) as well as body weight (apixaban and edoxaban) into account [13]. According to prior investigations, up to 50% of all patients prescribed NOACs were inappropriately dosed, the vast majority of patients being under-dosed [14][15][16][17]. This is of clinical relevance, as results from a meta-analysis of randomized controlled trials as well as several registries showed that off-label NOAC dosing is associated with worse clinical outcome [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Dosing of rivaroxaban, which is adjusted only according to kidney function, seems to be simpler than that of other DOACs, which is more limited by various factors (creatinine, weight, age, treatment with P-glycoprotein inhibitors). Consequently, prescribing this agent would reduce the risk of errors (Table 2) [5,[67][68][69][70], although dosing errors arising from the single criterion of kidney function have also been reported [71]. This is in line with different studies performed in real-life patients that have shown that despite rivaroxaban is underdosed in a significant proportion of patients, rates of thromboembolic and bleeding complications are low [72,73].…”
Section: Importance Of Appropriate Dosing Of Doacs In Elderly Patientsmentioning
confidence: 84%
“…Most of our prescriptions were appropriately dosed based on the CG formula (73%), in which 21% were overdosed, and only 6% were underdosed; this finding contradicts other studies. 6 , 15 , 18 , 19 A German study, for example, showed that in clinical practice, rivaroxaban was underdosed in 52% of the patients, which is frequently incoherent with the trial labelling. 19 Another retrospective Saudi study showed that 42% of rivaroxaban prescriptions had inappropriate doses, and 83% were underdosed.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 15 , 18 , 19 A German study, for example, showed that in clinical practice, rivaroxaban was underdosed in 52% of the patients, which is frequently incoherent with the trial labelling. 19 Another retrospective Saudi study showed that 42% of rivaroxaban prescriptions had inappropriate doses, and 83% were underdosed. 15 In clinical practice, HAS-BLED score and patient’s age might be considered when dosing rivaroxaban.…”
Section: Discussionmentioning
confidence: 99%